A nostalgia da forma poética do romance: alegorização barroca e tradição retórica n'O Ateneu de Raul Pompéia - Araújo, Francisco Magno Silva de (2017)
The present study proposes to analyze the stylistic primacy of Raul Pompéia’s O Ateneu (1888), seeking to show it as a novel that elects poetry as the creative material, making of it one of the most significant works within the Brazilian literary panorama. Along with a broad re-reading of the pertinent bibliography, which starts from the review of the book's critical fortune in correspondence with the reception theory, it seeks to show the mechanics of Sérgio's "chronic of homesickness" through three procedures: first, as an allegorical transposition of reality into the fable; second, as a poetic meta-language updated in the form of the novel; and, finally, as baroque recycling of old rhetorical codes in modern fictional prose.